Indoor abstract spaces :linking IndoorGML and LADM - Zlatanova, S. (2020)
In this paper we investigate the possible synergy between two different but related standards: OGC’s IndoorGML and ISO TC211’s LADM. Both (can) deal with 3D spaces with properties, constraints and associations attached and both can operate with abstract notations of space. But there are also differences, e.g. LADM is a conceptual model, while IndoorGML is also an actual XML schema (technical model), which can be used directly for data exchange and storage. Also, the scope is different; e.g. IndoorGML focuses on indoor spaces, while LADM addresses all spaces (in principle a complete subdivision of the countries territory, including outdoor, water and surface spaces). LADM models legal and administrative concepts such as use and ownership rights of spaces related to certain parties. IndoorGML puts emphasis on connectivity of spaces related to the navigability as one of the main use cases. These characteristics make the two standards quite complementary and this motivates our exploration in the combination of both. The spaces defined by LADM are the results of legal/administrative rights, restrictions, responsibilities (largest possible homogeneous spaces with respect to these RRRs). The space subdivision of IndoorGML is based on navigable areas and their connectivity. IndoorGML also recognizes other spaces, called abstract spaces. The paper will compare the space characteristics of the two models and will explore options to combine the models.